Strong and anisotropic magnetoelectricity in composites of magnetostrictive Ni and solid-state grown lead-free piezoelectric BZT–BCT single crystals. Issue 1 (1st March 2017) - Palneedi, Haribabu; Annapureddy, Venkateswarlu; Lee, Ho-Yong; Choi, Jong-Jin; Choi, Si-Young; Chung, Sung-Yoon; Kang, Suk-Joong L.; Ryu, Jungho
Abstract: Aimed at developing lead-free magnetoelectric (ME) composites with performances as good as lead (Pb)-based ones, this study employed (001) and (011) oriented 82BaTiO3 -10BaZrO3 -8CaTiO3 (BZT–BCT) piezoelectric single crystals, fabricated by the cost-effective solid-state single crystal growth (SSCG) method, in combination with inexpensive, magnetostrictive base metal Nickel (Ni). The off-resonance, direct ME coupling in the prepared Ni/BZT–BCT/Ni laminate composites was found to be strongly dependent on the crystallographic orientation of the BZT–BCT single crystals, as well as the applied magnetic field direction. Larger and anisotropic ME voltage coefficients were observed for the composite made using the (011) oriented BZT–BCT single crystal. The optimized ME coupling of 1 V/cm Oe was obtained from the Ni/(011) BZT–BCT single crystal/Ni composite, in the d32 mode of the single crystal, when a magnetic field was applied along its [100] direction. This performance is similar to that reported for the Ni/Pb(Mg1/3 Nb2/3 )O3 -Pb(Zr, Ti)O3 (PMN–PZT) single crystal/Ni, but larger than that obtained from the Ni/Pb(Zr, Ti)O3 ceramic/Ni composites. The results of this work demonstrate that the use of lead-free piezoelectric single crystals with special orientations permits the selection of desired anisotropic properties, enabling the realization of customized ME effects in composites.